Investigação de infecção por Leishmania spp em gatos (Felis catus) de área endêmica para as leishmanioses - Stephanie Karoline Pereira Passos (2016)
Visceral leishmaniasis, caused by the Leishmania infantum protozoa, is considered an endemic disease in Brazil. It is known that the dog is the main host and reservoir host for the disease. However, the cats role in the epidemiology of leishmaniasis is being questioned. This research aimed at surveying feline leishmaniasis cases and also at evaluating diagnostic techniques and the frequency of the disease caused by Leishmania infantum in a cattery. The sample consisted of 100 cats, randomly selected from a population of 250 animals. Each of them was identified through identity sketches and had a microchip subcutaneously implanted. After a thorough clinical examination, 5mL of blood were collected for hematological and biochemical profiles, immunochromatographic assays for leishmaniasis, FIV and FeLV diagnoses, and serological tests - ELISA and IIFT - for the detection of anti-Leishmania antibodies. Twenty-two cats, positive in both serological tests, were selected. Bone marrow biopsies were performed in order to prepare slides for Leishmania identification, for HSP70- PCR and kDNA-PCR assays, and for Leishmania cultures. Also, skin biopsies were performed for PCR assays. In the second stage of the experiment there were no positive results in the tests. Thus, using the Chi-square test and the Spearman correlation, the previous stage was analyzed in order to justify serology and inflammatory proteins results. A statistically significant association was found (p<0, 05) in the albumin (Spearman test) and in the creatinine (Chi-square test) categories. It is possible to demonstrate in this paper that the serological techniques (IIFT and ELISA) were not able to diagnose the disease in felines, and also that the albumin and creatinine variables presented positive correlations with serology.